1993
DOI: 10.3168/jds.s0022-0302(93)77718-8
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Response to Addition of Degradable Protein to a Low Protein Diet Fed to Midlactation Dairy Cows

Abstract: Midlactation Holstein cows (n = 24, 12 primiparous) were subjected to four dietary treatments arranged in six Latin squares. Cows were assigned to squares according to parity and previous production within parity. Diets contained 53 to 55% DM from corn silage, and the remaining DM was from concentrates. The basal diet contained 13.9% CP with 9.5% rumen-degraded and 4.4% undegraded intake protein. Three other treatments were formulated to give one diet with more degradable true protein than the basal (11.9% deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 9 publications
4
13
0
2
Order By: Relevance
“…The 12.1% CP diets resulted in higher rumen ammonia and plasma urea concentrations, possibly because of increased supply of rumen degradable N. It has been demonstrated that increased supply of dietary N and specifically rumen degradable N has a direct effect on rumen ammonia concentration and subsequently on levels of urea in the blood (Armentano et al 1993;Castillo et al 2001). SRU diets resulted in lower rumen ammonia and decreased plasma urea concentrations, especially at 10.9% CP, because of its controlled-release properties, which may indicate that SRU may carry a lower risk for toxicity 100 V.B.…”
Section: Discussionmentioning
confidence: 99%
“…The 12.1% CP diets resulted in higher rumen ammonia and plasma urea concentrations, possibly because of increased supply of rumen degradable N. It has been demonstrated that increased supply of dietary N and specifically rumen degradable N has a direct effect on rumen ammonia concentration and subsequently on levels of urea in the blood (Armentano et al 1993;Castillo et al 2001). SRU diets resulted in lower rumen ammonia and decreased plasma urea concentrations, especially at 10.9% CP, because of its controlled-release properties, which may indicate that SRU may carry a lower risk for toxicity 100 V.B.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that production of isoacids by microbes is related to potential release of amino acids (AA) and deamination from proteins in the rumen, and that this occurs when optimal rumen degradable proteins are consumed (Armentano et al, 1993;Yang et al, 2004). In the rumen, cellulolytic bacteria primarily use NH 3 -N while amylolytic bacteria prefer to use AA as they have a proteolytic activity.…”
Section: Isoacidsmentioning
confidence: 99%
“…The concentration of ammonia in the rumen is a function of both the rate of ruminal N degradation and the concentration of rumen degradable protein (RDP) above microbial needs and the amount of dietary energy available to the ruminal microorganisms (Hirstov et al, 2004). Increasing crude protein concentration or RDP percentage usually results in an increase of ruminal ammonia concentration (Armentano et al, 1993;Davidson et al, 2003). In the present study, supplements were isonitrogenous.…”
Section: Resultsmentioning
confidence: 90%